A checklist of the Coleoptera (Insecta) from Morelos, Mexico - Zaragoza-Caballero, Santiago; Rodríguez-Mirón, Geovanni M.; Vega-Badillo, Viridiana; González-Ramírez, Mireya; Zurita-García, Martín L.; Domínguez-León, Daniel E.; López-Pérez, Sara; Gutiérrez-Carranza, Ishwari G.; Cifuentes-Ruiz, Paulina; Pérez-Hernández, Cisteil X.; Del Valle, Enya Ramírez; Gutiérrez, Nayeli (Zootaxa, 2019)
Data from the literature and from specimens preserved at the Colección Nacional de Insectos (CNIN) Instituto de Biología, UNAM were used to compile a checklist of the fauna of Coleoptera of the state of Morelos, México. A sum of 70 families, 167 subfamilies, 361 tribes, 1,022 genera, and 2,606 species are recorded; from this 24 species are new records for Morelos. The State of Morelos ranks fourth in Coleoptera species richness for Mexico, following Veracruz (3,176 spp.), Oaxaca (2,148 spp.) and Chiapas (1,734 spp.). The checklist presented here provides a summary that can serve as a basis for future progress in the knowledge of Mexican Coleoptera.